Quantitative and qualitative dynamics of exotic and native blowflies ( Diptera: Calliphoridae) with migrations among municipalities - Moretti, T. C.; Coutinho, R. M. [UNESP]; Moral, R. A.; Ferreira, C. P. [UNESP]; Godoy, W. A. C. (Akademiai Kiado, 2013)
The population dynamics of blowflies (Diptera: Calliphoridae) has been investigated in studies combining different mathematical formalisms, with estimates of demographic parameters and spatial models. However, these applications are limited to laboratory data only. In this study, we investigated the population dynamics of three species of blowflies [ Chrysomya albiceps (Wiedemann), Chrysomya megacephala (F.) and Lucilia eximia (Wiedemann)] in a mathematical model that includes parameters estimated in the laboratory and population sizes estimated from field collections, in order to simulate the dynamics of local migration. The model combines experimental estimates of fecundity and survival with abundance data obtained in field collections, to analyze comparatively the population dynamics of the three blowfly species, taking into account the theoretical movement by individuals among municipalities with different urbanization profiles. The ecological patterns of oscillation observed depended on the municipality only for C. albiceps, a species with special demographic characteristics that are probably associated with predatory and cannibalistic behaviors. The bifurcation diagrams showed that intermediate migration rates stabilize populations. Although the proposed model considers only six municipalities in a closed system, the study was able to show different impacts of local migration on the quantitative and qualitative population behaviors, by using different connectivity levels arising from the different distances among areas.
Keywords: Chrysomya albiceps; Chrysomya megacephala; Forensic entomology; Lucilia eximia; Mathematical model; Population dynamics; Spatial structure